Completeness of Maternal Verbal Autopsy Through the Maternal Death Notification Application - Endah Purda Listya; Cahyono Hadi; Prima Dhewi Ratrikaningtyas (Jurnal Kebidanan, 2025)
Introduction: Maternal mortality in North Lampung remains high despite the implementation of the Maternal Perinatal Audit (AMP-SR). This study evaluates the completeness of maternal verbal autopsy data in the Maternal Death Notification (MDN) application. Objective: This study aims to evaluate the completeness of the completion of maternal verbal autopsy through the Maternal Death Notification application in the North Lampung district. Methods: A qualitative descriptive study with a single case design was conducted in January–March 2022 at the North Lampung Health Office, Kotabumi Udik, and Kubu Hitu Health Centers. Eight purposively selected informants, including health officials and midwives directly involved in MDN implementation, participated in in-depth interviews. Data were analyzed using Open Code software, complemented by document review. Results: The MDN application has been implemented at both health centers and hospitals, but several input and process components are incomplete. Some facilities rely on personal laptops, and several sections of the maternal verbal autopsy forms remain unfilled. Conclusion: Limited supervision and poor coordination contribute to incomplete data entry.